2008
DOI: 10.1212/01.wnl.0000319691.50117.54
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathologic correlates of white matter hyperintensities

Abstract: White matter hyperintensities (WMH) involve a loss of vascular integrity, confirming the vascular origin of these lesions. This damage to the vasculature may in turn impair blood-brain barrier integrity and be one mechanism by which WMH evolve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
290
3
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 305 publications
(322 citation statements)
references
References 28 publications
14
290
3
6
Order By: Relevance
“…We were particularly interested in the health variables as a large body of evidence suggests that WMH have a vascular aetiology (e.g., Jeerakathil et al, 2004;Wen & Sachdev, 2004;Young, Halliday, & Kril, 2008). Our findings suggest that the WMH-RT associations found here were related to ageing rather than other physical health comorbidities in the present sample.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…We were particularly interested in the health variables as a large body of evidence suggests that WMH have a vascular aetiology (e.g., Jeerakathil et al, 2004;Wen & Sachdev, 2004;Young, Halliday, & Kril, 2008). Our findings suggest that the WMH-RT associations found here were related to ageing rather than other physical health comorbidities in the present sample.…”
Section: Discussionmentioning
confidence: 72%
“…Although there is a broad literature relating increased IIV to neurobiological disturbance, the present results suggest that the association between RT measures and WMH is likely to be related to normal age associated deterioration rather than neuropathological decline relating to dementia up to six years following assessment. It is also important to note that the relationship between the RT metrics and WMH was not influenced RT variability and WMH in old age 15 when statistically adjusting for health measures including neurological conditions, depression, cardio-or cerebrovascular disease, cardiovascular risk factors, or APOE e4 status.We were particularly interested in the health variables as a large body of evidence suggests that WMH have a vascular aetiology (e.g., Jeerakathil et al, 2004;Wen & Sachdev, 2004;Young, Halliday, & Kril, 2008). Our findings suggest that the WMH-RT associations found here were related to ageing rather than other physical health comorbidities in the present sample.…”
mentioning
confidence: 72%
“…Childhood intelligence is the strongest predictor of late-life intelligence and accounts for about 40% of the variance in intelligence at age 78 . Magnetic resonance imaging (MRI)-detected white matter hyperintensities (WMH) (Young et al 2008) are associated with vascular risk factors (Murray et al 2005) and with reduced cognitive ability and dementia in older adults (Leaper et al 2001;Firbank et al 2007). We previously found that WMH contribute 14% of the variance in cognitive ability at age 78, that WMH are linked to hypertension , and it is now widely accepted that WMH are an imaging biomarker of vascular disease (Kearney-Schwartz et al 2009, Raz et al 2007, Fischer et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Ischemic stroke that occurs in the white matter often results in degeneration of OLs and demyelination (5,6). Consequently, patients with white matter stroke suffer from a wide range of neurological dysfunctions.…”
mentioning
confidence: 99%